Labor Market Institutions and the Cost of Recessions - Tom Krebs; Martin Scheffel (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper studies the effect of two labor market institutions, unemployment insurance (UI) and job search assistance (JSA), on the output cost and welfare cost of recessions. The paper develops a tractable incomplete-market model with search unemployment, skill depreciation during unemployment, and idiosyncratic as well as aggregate labor market risk. The theoretical analysis shows that an increase in JSA and a reduction in UI reduce the output cost of recessions by making the labor market more fluid along the job finding margin and thus making the economy more resilient to macroeconomic shocks. In contrast, the effect of JSA and UI on the welfare cost of recessions is in general ambiguous. The paper also provides a quantitative application to the German labor market reforms of 2003-2005, the so-called Hartz reforms, which improved JSA (Hartz III reform) and reduced UI (Hartz IV reform). According to the baseline calibration, the two labor market reforms led to a substantial reduction in the output cost of recessions and a more moderate reduction in the welfare cost of recessions in Germany.
Keywords: E21; E24; D52; J24; 330; labor market institutions; cost of recessions; German labor market reform